Literasi Inklusi Keuangan Digital Berbasis Ekonomi Syariah bagi Nelayan Ikan Depik (Endemik) Danau Laut Tawar - Mellyan Mellyan; Junaidi Junaidi; Sari Diana (Universitas Nurul Jadid, 2024)
The Depik Fishermen (Rasbora Tawarensis/Lepsotoma) in Lake Laut Tawar, Central Aceh, mostly still employ traditional systems in the process of selling Depik Fish. Introduction to digital marketing is needed for Depik fishermen to market this endemic fish to the public. The aim of this community service was to increase the income of Depik fishermen in Lake Laut Tawar and to explain various digital marketing strategies suitable for increasing sales of Depik fishermen in Lake Laut Tawar. The community service method used Participatory Action Research (PAR) with interview instruments, observations, seminars, and training to obtain desired results. The results of the community service successfully introduced digital marketing systems to Depik fishermen by creating Instagram accounts, opening shops on Shopee and Online Stores. Additionally, it introduced online Sharia financial platforms besides Banks, such as Investree, Ammana – Online Sharia Loans, Online P2P Lending Loans, BSalam, and others. There were also investment platforms like Amartha.com, specializing in SMEs, Bibit with its flagship product mutual funds, and crowdfunding systems like Tani Fund. However, there were some issues such as decreasing Depik catch results due to the use of floating cages, resorts along the lake, and the presence of Hoe fishermen. As for Depik fish catches, in the first quarter of 2021 it amounted to 12.602 tons, then increased in the second quarter to 18 tons, then decreased in the third quarter to 1.444 tons and significantly decreased again in the sixth quarter to 0.031 tons.